PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SDN 137 PALEMBANG PROGRAM STUDI PGSD - Feby Aimima; Henni Riyanti; Aqmarina Husnul Bayti; Nadiyah Kamilah; M.Lutfi Habibi; Ni Gusti Ketut Devi Handayani; Mahisa Rani; Devia Farasintia Anisa (STKIP Subang, 2026)
This study aimed to determine the effect of the Team Games Tournament (TGT) cooperative learning model on the Indonesian language learning outcomes of fifth-grade students at SDN 137 Palembang, Elementary School Teacher Education Program (PGSD). The study employed a quantitative approach using a one-group pretest-posttest design. The research subjects consisted of 13 fifth-grade students. Data were collected through learning achievement tests, affective assessments, and psychomotor assessments. The findings showed that the implementation of the TGT model significantly improved students’ learning outcomes. The average pretest score was 72, with a learning mastery percentage of only 30.77%, where only 4 students achieved the minimum mastery criterion. After the implementation of the TGT model, the average posttest score increased to 87.69, with the mastery level reaching 100%. The improvement in learning outcomes was also supported by an N-Gain score of 0.56, which was categorized as moderate. In addition to cognitive improvement, the TGT model also had a positive impact on students’ cooperation, self-confidence, and learning skills during the instructional process. These findings indicate that the TGT cooperative learning model is effective for Indonesian language learning in elementary schools because it creates an active, competitive, and collaborative learning atmosphere that encourages students to become more motivated in understanding the learning materials.